Switch from sequestering to anti-CD20 depleting treatment: disease activity outcomes during wash-out and in the first 6 months of ocrelizumab therapy. (January 2022) - Signoriello, Elisabetta; Lus, Giacomo; Bonavita, Simona; Lanzillo, Roberta; Saccà, Francesco; Landi, Doriana; Frau, Jessica; Baroncini, Damiano; Zaffaroni, Mauro; Maniscalco, Giorgia Teresa; Curti, Erica; Sartori, Arianna; et al.
Objectives: Switching between treatments is an opportunity for patients with multiple sclerosis (MS) to ameliorate disease control or safety. The aim of this study was to investigate the impact of switching from fingolimod (FTY) or natalizumab (NTZ) to ocrelizumab (OCR) on disease activity. Methods: We retrospectively enrolled 165 patients treated with OCR from 11 MS centres. We assessed the association of demographic and clinical characteristics on relapse rate (RR) and activity on magnetic resonance imaging (MRI) during wash-out and after 6 months of treatment with OCR through univariable and multivariable negative binomial regression models. Results: We registered a total of 35 relapses during the wash-out period. Previous treatment with FTY, relapses in the previous year, and relapsing-remitting course were associated with higher RR. In the first 6 months of OCR, 12 patients had clinical or MRI disease activity. Higher Expanded Disability Status Scale (EDSS) and higher lymphocyte count at OCR start were associated with a reduced probability of relapse. Discussion and Conclusion: This study confirms that withdrawal from sequestering agents as FTY increases the risk of relapses in the wash-out period. Nevertheless, starting OCR before achieving complete immune reconstitution could limit its effectiveness in the first 6 months probably because trapped lymphocytes escape the CD20-mediated depletion.